Perspectives on care at home for older people - Ceci, Christine; Kristin Bjornsdottir; Purkis, Mary Ellen (New York : Routledge, 2012)
'This volume focuses on how high quality care is provided and the practices and policies that support this. It will offer case studies (both policy- and practice-oriented empirical studies) from countries that share a basic orientation to social welfare: Canada, Denmark, Finland, Iceland, Sweden and the United Kingdom. This book will be essential reading for students, practitioners and researchers who wish to understand diverse problems in service provision for the elderly and the complexities of policy responses in different health and social care contexts'--
Aging, independence, and community / Mary Ellen Purkis -- Homecare and frail older people : relational extension and the art of dwelling / Joanna Latimer -- Homes for care : reconfiguring care relations and practices / Isabel Dyck and Kim England --'To work out what works best' : what is good in home care? / Christine Ceci -- Bringing it all back home : the (re)domestication and (de)medicalization of care in the UK / Davina Allen -- Assisting the frail elderly to live a good life through home care practice / Krist Bj$1'Xr(Bnsd{u2BF4}tir -- Who can be against quality? : a new story about home-based care : NPM and governmentality / Hanne Marlene Dahl -- Creating home care recipients : using categorization as a tool in home care case management / Anna Olaison -- The making of medico-managerial care work culture in public home care for the elderly / Lea Henriksson and Sirpa Wredes
Keywords: Home care services; Aged; Health Services for the Aged; Long-Term Care -- methods